Variation Parameters of The 2004 Indian Ocean Tsunami Model for Tsunami Prone Area Mapping in The Northern Part of Aceh Province - Siti Rohaya Syifa; Abdi Jihad; Muksin Umar; Vrieslend Haris Banyunegoro; Andi Azhar Rusdin (Indonesian Journal on Geoscience, 2023)
A total of ten tsunami events occurred in Aceh Province from 1991 to 2012. This condition confirms that AcehProvince is very vulnerable to tsunami hazards. In 2004, a tsunami occurred due to the activity of the subduction zone onthe west coast of Aceh with a magnitude of Mw 9.3. Since the 2004 tsunami, research on tsunamis has increased. The aimof this study is to reconstruct the 2004 tsunami models, to find out which models are suitable for the events of 2004. Thereare at least five models of earthquake source faults used for tsunami modeling in this study. The tsunami modeling wascarried out numerically using the Tohoku University’s Numerical Analysis Model Investigation (TUNAMI) programme.The maximum height obtained from the modeling is 58,05 m at the shoreline. The maximum height obtained from thebest model is 17,73 m on land. The M5 fault model produced a tsunami height model that best matches the observationresults validated by lowest RMS and highest correlation coefficient values Keywords: tsunami height, fault model, correlation coefficient, RMSE